1973
DOI: 10.1177/104438947305400403
|View full text |Cite
|
Sign up to set email alerts
|

Natural Parents as Partner in child Care Placement

Abstract: A report of a unique project in child care describes how strengthening the bonds of familial relationships results in improved parental functioning

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Staff and volunteers also experienced personal and professional benefi ts from being involved in the playgroups. These fi ndings are consistent with other programmes of this nature which report benefi ts including increased feelings of support and understanding, improved self-confi dence and parenting confi dence, more involvement in aspects of their child's development, improvement in communication, as well as developing new friendships and social networks (Gibbs and Thorpe, 1975;Simmons et al, 1973;Thomson and Thorpe, 2004). The opportunity for parents to learn new parenting skills and to practise them with children on a regular basis under supervision is a key strength of the Parents Plus Playgroups.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Staff and volunteers also experienced personal and professional benefi ts from being involved in the playgroups. These fi ndings are consistent with other programmes of this nature which report benefi ts including increased feelings of support and understanding, improved self-confi dence and parenting confi dence, more involvement in aspects of their child's development, improvement in communication, as well as developing new friendships and social networks (Gibbs and Thorpe, 1975;Simmons et al, 1973;Thomson and Thorpe, 2004). The opportunity for parents to learn new parenting skills and to practise them with children on a regular basis under supervision is a key strength of the Parents Plus Playgroups.…”
Section: Discussionsupporting
confidence: 88%
“…The purpose of the review was to identify programme evaluations of groups for parents whose children are in care; however, the search yielded only three such papers (Charbonneau and Kaplan, 1989;Simmons et al, 1973;Thomson and Thorpe, 2004). The search criteria were then expanded to include descriptions of specifi c interventions for parents whose children have been placed in care and was not limited to evaluations of programmes and interventions.…”
Section: Characteristics Of Programmes For Parents Whose Children Arementioning
confidence: 99%
See 2 more Smart Citations
“…He found that boys without a father living with them had idealistic, fantasy pictures of their fathers. Simmons et al (1973) also found that post-divorce children who had strong self-concepts had stronger ties to the natural family than those who did not. The authors suggest that the normal process of continuity and integration (self-concept) are often interrupted when a child loses contact with one of the parents.…”
Section: Discussionmentioning
confidence: 88%